Bloom : a story of fashion designer Elsa Schiaparelli - Maclear, Kyo, 1970- (Harper, an imprint of HarperCollinsPublishers, 2018)
By the 1930s Elsa Schiaparelli had captivated the fashion world in Paris, but before that, she was a little girl in Rome who didn't feel pretty at all. Bloom: A Story of Fashion Designer Elsa Schiaparelli is the enchanting story for young readers of how a young girl used her imagination and emerged from plain to extraordinary.